Potential of using photovoltaic systems to power underwater fishing lights in small-scale fishing vessel in Indonesia - I Made Aditya Nugraha; Febi Luthfiani; I Gusti Made Ngurah Desnanjaya; Jhon Septin Mourisdo Siregar; Lebrina Ivantry Boikh (Institute of Advanced Engineering and Science, 2023)
The limited stock and uncertainty of fuel prices as a source of driving the main engine and generator on ships greatly affect the lives of fishermen in Indonesia. Even though there is a policy in the form of assistance from the government in the form of subsidies, fishermen still feel doubtful about being able to get such assistance. To overcome this and with the potential of solar energy in Indonesia, as well as a manifestation of appropriate technology and blue economy policies, a photovoltaic system is made that is combined with underwater lights as a fishing tool. Activities are carried out by measuring environmental conditions and the energy that comes out of the PV system and giving questionnaires to the fishermen. The results showed that the use of PV systems combined with underwater lights in fishing activities gave good results. The result of electrical energy that can be generated is 393.24 Wh/day and can meet the ship’s electricity needs for 4 days. This result is also supported by the Wilcoxon test results for technical, economic, environmental, health, and safety aspects with a significance value of 0.001 (p<0.05).